Molecular Characterization and Moxifloxacin Susceptibility of Clostridium difficile - Sarah Mizrahi; Zohar Hamo; Maya Azrad; Avi Peretz (MDPI AG, 2019)
In recent years, the incidence and severity of Clostridium difficile infections has increased. Additionally, resistance of C. difficile to frequently used antibiotics is rising. To improve our understanding of C. difficile, there is a need for molecular characterization of different strains and antibiotic resistance testing. We investigated the efficacy of GenoType CDiff kit (Hain Lifesciences) in identification of C. difficile and its various strains in northern Israel. The kit involves a molecular assay that detects C. difficile from stool samples or colonies and identifies the different strains and mutations in the gyrA gene that cause moxifloxacin resistance. Forty-nine C. difficile positive samples were examined by the kit following DNA extraction from both colonies and stool. The identification rate (95.9%) of C. difficile was much higher when DNA was extracted from colonies, compared to extraction from stool (46.9%). Low frequencies of ribotype027 strain (2%) and of ribotype078 strain (4%) were found. There was a high concordance between genotype (mutation in gyrA) and phenotype (Etest) for moxifloxacin resistance (Kappa = 0.72). A high percentage of moxifloxacin-resistant strains was found. Our findings indicate that the GenoType CDiff kit is very effective in characterization of C. difficile strains and less effective for identification of C. difficile directly from stool samples.